Sadd al-Zari'ah and Extra-Judicial Divorce: A Critical Discourse Analysis of MUI Fatwa and KHI Legal Frameworks - Ahmad Agum Manoppo; Firman Muhammad Arif; Muhammad Tahmid Nur (Universitas Islam Negeri Palopo, 2025)
The objective of this research is to examine the